The Need of Other Elements - Aragón Vargas, Luis Fernando (2016)
A number of natural drinks and ingredients used in hydration beverages have been discussed, focusing on their effectiveness for post-exercise rehydration. Because of excess diuresis, complete, rapid, and sustained restoration of fluid balance remains a challenge. The most effective ingredient to promote fluid retention is sodium, although the possible merits of milk protein, creatine, and additional potassium were presented. Cultural preferences may lead some individuals to rehydrate with Roselle infu-sion, mineral water, or coconut water; doing so has been shown not to deter from the goal of restoring body fluid. Skimmed milk has been shown to be more effective than conventional sports drinks and water and may be a good rehydration choice in the absence of lactose intolerance. Furthermore, sports drinks with added milk or whey protein, which may be desirable to provide amino acids and help recov-ery, have been shown not to impair rehydration. The use of caffeinated beverages, although favored by many consumers and shown not to impair chronic hydration, remains more of an open question for quick post-exercise rehydration. Evidence was provided to show why regular beer is contraindicated when effective post-exercise rehydration is desired, together with evidence about the serious limitations associ-ated with the use of glycerol.